1990
DOI: 10.1071/pp9900653
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Imposition of Water Stress Alters the Accumulation of Nitrogen-Containing Solutes by Wheat Seedlings

Abstract: A rapid water stress, imposed by withholding water under a high transpirational demand or by the application of polyethylene glycol (PEG), resulted in the accumulation of glutamine, asparagine and valine in amounts equal to or greater than that of proline. However, progressive water stress imposition resulted in proline and glycinebetaine being the dominant accumulated compounds of those measured. PEG had an apparently specific effect on amino acid accumulation, particularly of the amide forms. With some excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…When plants were exposed to varying levels of plant moisture stress the concentration of organic acids (but not amino acids) in xylem fluid during midday increased with Xt. The increase in organic N commonly reported in leaf tissue or whole plants with increasing plant moisture stress (Naidu et al 1990, Rabe 1990, Ranieri et al 1989) did not occur. However, increased concentrations of organic acids in conjunction with complexed cations in xylem fluid (Clark et al 1986) may also facilitate turgor maintenance in leaves.…”
Section: Discussionmentioning
confidence: 74%
“…When plants were exposed to varying levels of plant moisture stress the concentration of organic acids (but not amino acids) in xylem fluid during midday increased with Xt. The increase in organic N commonly reported in leaf tissue or whole plants with increasing plant moisture stress (Naidu et al 1990, Rabe 1990, Ranieri et al 1989) did not occur. However, increased concentrations of organic acids in conjunction with complexed cations in xylem fluid (Clark et al 1986) may also facilitate turgor maintenance in leaves.…”
Section: Discussionmentioning
confidence: 74%
“…Reynoso and Gamboa (1982) found a linear relation between the concentration of proline added to the medium and tolerance to salt in freshwater alga Chlamydomonas. In wheat seedlings (Naidu et al 1990) and in durum wheat (Bajji et al 2001) a positive correlation was observed between proline levels and osmotic potential, and it was concluded that proline is an osmoregulatory component. It was also reported that the net accumulation of proline as an organic compatible solute contributed to osmotic adjustment in saline conditions (Heuer 1995), and in water stress environments (Zhul et al 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Their approach was similar to ours in that they inhibited ABA synthesis using either FLU (in barley) or the flacca mutant of tomato, but they found that neither treatment altered the extent of Pro accumulation. Although it is possible that the different results in the two studies are due to species or organ differences, the nature and rate of low qW imposition might also be involved (Naidu et al, 1990). In the Stewart and Voetberg study, detached leaves were dehydrated rapidly by either floating on PEG (barley) or air-drying on the laboratory bench (tomato).…”
Section: Dlscusslonmentioning
confidence: 99%